SPATIAL VARIATION OF ANNUAL CYCLE AND SEMI-ANNUAL CYCLE RAINFALL IN NORTH SUMATRA - AMRI (NIM : 12813601), SAYFUL
Rainfall pattern was very important for season prediction in Indonesian Maritime Continent. There were 2 main methods for determining rainfall pattern in Indonesian Maritime Continent, PCA (Principal Component Analysis) and harmonic analysis. Harmonic analysis method was known more capable to be applied on complex topography region. This condition was also found in North Sumatra, this was due to the region being on the path of Bukit Barisan Mountains. Determination of rainfall pattern in North Sumatra was done by analyzing annual and semi-annual cycle which was obtained from harmonic analysis. Ratio value (comparison between annual amplitude with the amount of annual and semi-annual amplitude) was calculated and plotted into the map to obtain spatial variation and delineation of the region. While the factors that cause spatial variation was studied by analyzing of moisture transport and convergence value which was obtained from Era Enterim reanalysis data. Result showed North Sumatra can be divided by 5 regions of rainfall cycle, region 1 (semi-annual cycle dominant), region 2 (semi-annual cycle slightly dominant) region 3 (annual cycle slightly dominant), region 4 (annual cycle dominant) and region 5 (annual cycle very dominant). The spatial variation was indicated due to influence of Bukit Barisan Mountains which become barrier mechanism of moisture transport in North Sumatera.